Generator Magnet Permanen Sebagai Pembangkit Listrik Putaran Rendah - Prasetijo, Hari; Ropiudin, Ropiudin; Dharmawan, Budi (Jenderal Soedirman University, 2012)
Development renewable energy as electrical energy need to be followed by provision of low speed generator, especially forÂ small-scale use of alternative energy. This study discusses the design of low speed synchronous generator using permanent magnetsÂ for producing magnetic flux in the rotor. Stator coils are designed so that on the rotation of 500 rpm generator can produce 5 wattsÂ output power at 3 phase voltage 12 Vac.